Clinical outcomes of colistin methanesulfonate sodium in correlation with pharmacokinetic parameters in critically ill patients with multi-drug resistant bacteria-mediated infection: A systematic review and meta-analysis - Ji-young Son; Semi Kim; Tuğçe Porsuk; Sooyoung Shin; Yeo Jin Choi (Journal of Infection and Public Health, 2024)
Background: Colistin is a viable option for multidrug resistant gram-negative bacteria emerged from inappropriate antibiotic use. Nonetheless, suboptimal colistin concentrations and nephrotoxicity risks hinder its clinical use. Thus, the aim of this study is to investigate clinical outcomes in correlation with pharmacokinetic differences and infection types in critically ill patients on intravenous colistin methanesulfornate sodium (CMS). Methods: A systematic literature search of Embase, Google Scholars, and PubMed was performed to identify clinical trials evaluating pharmacokinetic parameters along with clinical outcomes of CMS treatment from inception to July 2023. The pooled analyses of clinical impact of CMS on nephrotoxicity, mortality, clinical cure, and colistin concentration at steady state (Css,avg) were performed. This study was registered in the PROSPERO (CRD 42023456120). Results: Total of 695 critically ill patients from 17 studies were included. The mortality was substantially lower in clinically cured patients (OR 0.05; 95% CI 0.02 – 0.14), whereas the mortality rate was statistically insignificant between nephrotoxic and non-nephrotoxic patients. Inter-patient variability of pharmacokinetic parameters of CMS and colistin was observed in critically ill patients. The standard mean differences of Css,avg were statistically insignificant between clinically cure and clinically failure groups (standard mean difference (SMD) −0.25; 95% CI −0.69 – 0.19) and between nephrotoxic and non-nephrotoxic groups (SMD 0.67; 95% CI −0.27–1.61). The clinical cure rate is substantially lower in pneumonia patients (OR 0.09; 95% CI 0.01 – 0.56), and pharmacokinetic parameters pertaining to microbiological cure were different among strains. Conclusion: The mortality rate was substantially lower in clinically cured patients with CMS. However, no significant differences in Css,avg of colistin were examined to determine the impact of pharmacokinetic differences on clinical outcomes including mortality rate and nephrotoxicity risk. Nevertheless, the clinical cure rate is substantially lower in patients with respiratory infection than patients with urinary tract infection.